ANALYSIS OF THE WAYS OF BYPASSING THE TOOLS FOR THE THREATS PREVENTION AND RESEARCHING COUNTERING METHODS - Opanovych, Maksym (Science-based technologies, 2024)
This study examines the evasion techniques employed by Advanced Persistent Threat (APT) groups that bypass traditional defenses such as antivirus software and endpoint detection and response (EDR) systems. The focus is on techniques such as obfuscation, encryption, and exploitation of security tool vulnerabilities, which have been identified as significant challenges to effective threat detection. It examines how attackers use Living Off The Land Binaries and Scripts (LOLBAS) to manipulate built-in system tools for stealth attacks, seamlessly combining malicious activity with legitimate processes to avoid detection. The role of security information and event management (SIEM) systems in improving detection capabilities is also discussed. SIEM systems stand out for their ability to collect and analyze security data across a network, providing a holistic view that helps to identify potential threats and breaches early, thereby strengthening an organization’s security posture. Vulnerabilities in EDRs and antivirus solutions themselves are analyzed, showing how they can be exploited to disable or bypass these critical protections, leaving systems vulnerable. In addition, the development of malware generators using machine learning techniques is discussed. These tools, which are capable of creating adaptive malware designed to bypass current security measures, are recognized as marking a complex evolution in offensive capabilities. To combat these threats, a comprehensive security strategy is proposed that incorporates the concepts of zero trust, defense in depth, and the principle of security enhancement. According to the zero-trust model, all access requests, regardless of their origin, must be strictly verified. Defense-in-depth is characterized by the implementation of multiple layers of security in the IT environment, while the principle of hardening focuses on strengthening systems and applications to reduce vulnerabilities and the number of attack vectors.